Respostas
respondido por:
2
Resposta:
Explicação passo-a-passo:
. Reduza a uma só potência:
.
a) = (1/5)^(2-5-1) = (1/5)^(2-6) = (1/5)^-4
.
b) = (- 7)^(12+4) = (- 7)^16
.
c) = (2/3)^(2.4) : (2/3)^-3
. = (2/3)^8 : (2/3)^-3
. = (2/3)^8-(-3) = (2/3)^(8+3) = (2/3)^11
.
d) = (- 1/2)^(3+2) / (- 1/2)^(3.2)
. = (- 1/2)^5 / (- 1/2)^6
. = (- 1/2)^(5-6) = (- 1/2)^-1 = (- 2)¹ = - 2
.
(Espero ter colaborado)
.
.
sueliinm:
Muito obrigada
Perguntas similares
6 anos atrás
6 anos atrás
6 anos atrás
8 anos atrás
8 anos atrás
9 anos atrás
9 anos atrás
9 anos atrás